Critical success factors in introducing e-learning. (11th June 2007) - Luarn, Pin; Chen, Max I Jen; Lo, Peter Kai Yang
Electronic learning (e-learning) facilitates learning activities and allows the user to learn at anytime and in any location. In the past, little attention has been given to the assessment of Critical Success Factors (CSFs) in e-learning. We explored the CSFs related to the promotion of e-learning. Following preliminary in-depth interviews of 20 practitioners, a questionnaire was developed and completed by 394 employees enrolled in e-learning programmes. An analysis showed that four factors (real-time and complete information, personalised interface, interface friendliness, and entertaining and interactive functions) contributed a total variance of 56% in the CSFs. We also found that employees' learning performance had the most important impact on their positive evaluation of e-learning. Enhancing the function of information technology systems will improve the users' perception and adoption of e-learning. A positive circle is created in which the enthusiasm for e-learning leads to its greater adoption by employees and increases the probability of successful outcomes.